Work behavior from the Quranic perspective - Zainal Adnan Ahmad Amri, Mastor Khairul Anwar, Kasan Hasnan, Mohamad Hamzah Firdaus, (Universiti Pendidikan Sultan Idris, 2017)
Work behavior from the Quranic perspective by Zainal Adnan Ahmad Amri, Mastor Khairul Anwar, Kasan Hasnan, Mohamad Hamzah Firdaus,